Risk Analysis in Healthcare Organizations: Methodological Framework and Critical Variables - Pascarella G; Rossi M; Montella E; Capasso A; De Feo G; Botti Snr G; Nardone A; Montuori P; Triassi M; D'Auria S; Morabito A (Dove Medical Press, 2021)
Giacomo Pascarella,1 Matteo Rossi,2 Emma Montella,3 Arturo Capasso,2 Gianfranco De Feo,1 Gerardo Botti Snr,1 Antonio Nardone,3 Paolo Montuori,3 Maria Triassi,3 Stefania D'Auria,4 Alessandro Morabito5 1Scientific Directorate, Istituto Nazionale Tumori "Fondazione G. Pascale", IRCCS, Napoli, Italy; 2Wroclaw School of Banking Wyższa Szkoła Bankowa, Wrocalw, Poland; 3Department of Public Health, Università Federico II, Napoli, Italy; 4Department of Health Management, Istituto Nazionale Tumori, "Fondazione G. Pascale", IRCCS, Napoli, Italy; 5Thoracic Department, Istituto Nazionale Tumori "Fondazione G. Pascale" IRCCS, Napoli, ItalyCorrespondence: Giacomo PascarellaScientific Directorate, Istituto Nazionale Tumori "Fondazione G. Pascale", IRCCS, Via Mariano Semmola, 52, Napoli, 80131, ItalyEmail g.pascarella@istitutotumori.na.itPurpose: A risk assessment matrix is a widely used tool for analyzing, assessing and setting priorities in risk management in many fields. This paper overviews critical variables, advantages, disadvantages, strengths and weaknesses of this tool, according to the ISO 31000 risk management framework.Results: Risk assessment is one of the key stages in the Risk Management Process and involves specific steps: identifying hazards, analyzing and evaluating all possible risks. Several methods are developed to assess risks in the literature. A risk matrix method, also called "decision matrix risk assessment (DMRA) technique", is a systematic approach used to determine the risk level and to compare different risks and define which threats need to be controlled first. The actors involved in risk assessment are called on to manage different issues related to the choice of the most appropriate methodological approach, the assessment of the adequacy of the existing control measures, the articulation of risk consequence domains, the definition of the impact-consequences, the explanation of risk likelihood scales and the development of a risk matrix.Conclusion: We highlighted a number of recommendations in order to address these issues, especially useful when healthcare organizations provide insufficient guidance on how to use risk matrices as well as what to do in response to the existing criticisms on their use.Keywords: healthcare risk analysis, risk matrix, consequences-likelihood analysis